Penanaman Sikap Toleransi Melalui Materi IPS Tema 7 Kelas IV SDN Kedawong - Aminatus Sholihah; Hawwin Fitra Raharja (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
This study raises the issue of the lack of tolerance in fourth grade students at SDN Kedawong Diwek Jombang. The purpose of this study was to determine the results of inculcating an attitude of tolerance in students through social studies material Theme 7 Subtheme 1 Class IV SDN Kedawong Diwek Jombang. This research uses a qualitative approach with the type of case study research. The subjects of this study were school principals, fourth grade teachers and fourth grade students. The data collection method used is the method of observation, interviews and documentation. The validity of the data was obtained by using source triangulation, time triangulation and technical triangulation. The results showed that; 1) Inculcating an attitude of tolerance in students through Social Studies material Theme 7 Sub-theme 1 is not only done once in teaching and learning activities but must be made habituation during the process of daily teaching and learning activities. 2) In an effort to cultivate an attitude of tolerance, school principals and teachers instill an attitude of tolerance through school policies, namely by formulating a vision, mission, and goals. In addition, school regulations related to tolerance, through routine activities, example, and spontaneous activities. 3) The results reflected in the cultivation of an attitude of tolerance at SDN Kedawong are mutual respect and know each other whoever they are, be it teachers, other employees and also their own students, say greetings or shake hands when meeting teachers, enthusiasm for cooperation, mutual help, and mutual support. help in the school environment.